Shenkang injection combined with alprostadil for chronic renal failure: A systematic review and meta-analysis - Xie, Feng; Zhang, Tiantian; Zhang, Pu; Qu, Xinliang; Li, Min; Lan, Wei (Frontiers in Medicine, 2023)
Objective To systematically evaluate the clinical efficacy and safety of Shenkang injection (SKI) combined with alprostadil in the treatment of chronic renal failure (CRF). Method Randomized controlled trials (RCTs) of Shenkang injection combined with alprostadil in CRF treatment were investigated by retrieving a total of 7 databases including CNKI, Wanfang database, VIP, CBM, PubMed, Embase and Cochrane Library, with the search time ranging from 2012 to now. Revman 5.2 software was used for data analysis, and Cochrane bias risk tool was used to evaluate the quality of the included literature. The final results were represented by relative risk (RR), mean difference (MD) and 95% confidence interval (95% CI). Results A total of 20 RCTs and 1,573 patients were included in this study. Meta-analysis showed that the overall response rate (ORR) of the treatment group was superior to the control group [RR = 0.20, 95% CI (0.16, 0.25), P < 0.00001]. Compared with the control group, the treatment group achieved favorable improvement in terms of the creatinine clearance rate (Ccr) [MD = 9.48, 95% CI (8.73, 10.24), P < 0.00001], serum creatinine (Scr) [MD = −55.12, 95% CI (−63.42, −46.82), P < 0.00001], quantitative urine protein (Upro) [MD = −0.48, 95% CI (−0.53, −0.43), P < 0.00001], and blood urea nitrogen (BUN) [MD=-3.73, 95% CI (−4.08, −3.3) 7, P < 0.00001]. There was no statistical difference in the incidence of adverse reactions in each group. Conclusion Currently, Shenkang injection combined with alprostadil has been widely used in clinical treatment of CRF due to the certain effect superior to other methods. However, its specific efficacy and safety need to be further verified through numerous large-scale clinical trials.